Review of the Neotropical genus Pseudosympycnus (Diptera: Dolichopodidae), with description of six new species from Brazil and Peru - Soares, Matheus Mickael Mota; Capellari, Renato Soares (Zootaxa, 2020)
The Neotropical stolidosomatine genus Pseudosympycnus Robinson (Diptera: Dolichopodidae) is reviewed and contains 12 species, including six new species that herein are described and illustrated: P. araza sp. nov. (Peru, department of Cusco), P. bickeli sp. nov. (Brazilian States of Pará and Roraima), P. latitibia sp. nov. (Brazilian States of Minas Gerais, Rio de Janeiro and São Paulo), P. maroaga sp. nov (Brazilian State of Amazonas), P. robinsoni sp. nov. (Brazilian State of Acre), and P. sehnali sp. nov. (Brazilian State of Amazonas). All species are diagnosed, male and female terminalia of the genus are illustrated for the first time, high-resolution images of relevant characters are presented and an identification key to males is provided. © 2020 Magnolia Press.